The Influence Of Transformational Leadership Style On Employee Performance In The Public Works Service And Spatial Planning Of Asahan Regency - Sujarwo; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
This study aimed to analyze the effect of Transformational Leadership Style on Employee Performance at the Public Works and Spatial Planning Office of Asahan Regency. This research used a quantitative associative causal method with a simple linear regression approach to examine the influence of the independent variable on the dependent variable. The study was conducted with a population of 145 employees, and the sampling technique used was saturated sampling, where all members of the population were included as the sample. Data were collected through questionnaires distributed to employees, covering the entire population. The results of the regression test showed that Transformational Leadership Style had a positive and significant effect on Employee Performance, with a regression coefficient of 0.963, meaning that each one-point increase in Transformational Leadership Style would increase Employee Performance by 0.963 points. The coefficient of determination test produced an R Square value of 0.769, indicating that 76.9% of the variation in Employee Performance could be explained by the Transformational Leadership Style variable. The t-test produced a t-value of 21.836 > t-table 1.65558, and a significance value of 0.000 < 0.05, indicating that Transformational Leadership Style had a significant effect on Employee Performance. Overall, this study concluded that the implementation of Transformational Leadership Style could improve Employee Performance at the Public Works and Spatial Planning Office of Asahan Regency.